A sensitive ERK fluorescent probe reveals the significance of minimal EGF-induced transcription - Zhang Weisheng; Jun Nakayama; Yukino Inomata; Shigeki Higashiyama; Toru Hiratsuka (Cell Structure and Function)
Extracellular signal-regulated kinase (ERK) regulates multiple cellular functions through distinct activation patterns. Genetically encoded fluorescent probes are instrumental in dissecting the ERK activity dynamics in living cells. Here we modified a previously reported Förster resonance energy transfer (FRET) probe for ERK, EKAREN5 by replacing its mTurquoise2 and YPet sequences with mTurquoise-GL and a synonymous codon variant of YPet, respectively. The modified biosensor, EKAREN5-gl, showed an increased sensitivity to EGF-induced ERK activation responding to a very low dose (20 pg/ml) of EGF stimulation. We quantitatively characterized two FRET-based ERK probes, EKAREN5 and EKAREN5-gl, and a subcellular kinase translocation-based probe, ERK-KTR. We found the three biosensors differently respond to EGF stimulations with different intensity, duration, and latency. Furthermore, we investigated how the minimal EGF-induced ERK activation affects the downstream transcription in HeLa cells by comprehensive transcriptional analysis. We found the minimal ERK activation leads to a distinct transcriptional pattern from those induced by higher ERK activations. Our study highlights the significance of sensitive fluorescent probes to understand cellular signal dynamics and the role of minimal ERK activation in regulating transcription. Key words: fluorescent probe, ERK, FRET, KTR